Digital History dan Kesiapan Belajar Sejarah di Era Revolusi 4.0 - Anis, Mohamad Zaenal Arifin; Mardiani, Fitri; Fathurrahman, Fathurrahman (Universitas Hamzanwadi, 2022)
Tracing the life of the Industrial Revolution 4.0 era brings significant changes in the order of human life today. The atmosphere of the Covid-19 Pandemic also adds to the strangeness of life problems seen from the limitations of human life access and interaction. Education is still the spearhead in preparing the nation's next-generation that is adaptive, creative, innovative, and highly competitive in the rapid development of the times because the education sector focuses on facing life in the digital age. This study aims to analyze the course of history learning in the era of industrial revolution 4.0 and the use of digital history as a source of history in digital form to prepare for the era of technological disruption in history learning. The qualitative descriptive method consists of data collection, data reduction, presentation of the conclusion, and testing that the data is valid using triangulation techniques and sources. The research subjects were 100 students in semesters two, four, and six in a history education study program active in online lectures. Through the analysis in this study, it can be understood that there are obstacles to the implementation of online learning by students, especially in using learning resources. In addition, it is known that using digital history following the learning objectives is not optimal. They optimize the use of digital learning resources in history learning during the Covid-19 pandemic, providing flexibility and independence in learning. Students are invited to explore, create, and study more deeply about digital history by learning resources through digital history.Menelusuri kehidupan era Revolusi Industri 4.0 membawa perubahan signifikan dalam tatanan kehidupan manusia saat ini. Suasana Pandemi Covid-19 juga menambah keanehan permasalahan kehidupan dilihat dari keterbatasan akses dan interaksi kehidupan manusia. Pendidikan masih menjadi ujung tombak dalam mempersiapkan generasi penerus bangsa yang adaptif, kreatif, inovatif, dan berdaya saing tinggi di tengah pesatnya perkembangan zaman karena dunia pendidikan fokus menghadapi kehidupan di era digital. Penelitian ini bertujuan untuk menganalisis jalannya pembelajaran sejarah di era revolusi industri 4.0 dan pemanfaatan Sejarah Digital sebagai sumber sejarah dalam bentuk digital untuk mempersiapkan era disrupsi teknologi dalam pembelajaran sejarah. Metode deskriptif kualitatif terdiri dari pengumpulan data, reduksi data, penyajian kesimpulan, dan pengujian keabsahan data menggunakan teknik triangulasi dan sumber. Subyek penelitian ini adalah 100 mahasiswa semester dua, empat, dan enam di prodi pendidikan sejarah yang aktif dalam perkuliahan online. Melalui analisis dalam penelitian ini, dapat dipahami bahwa terdapat kendala dalam pelaksanaan pembelajaran online oleh peserta didik, khususnya dalam menggunakan sumber belajar. Selain itu, diketahui bahwa penggunaan sejarah digital sesuai dengan tujuan pembelajaran belum optimal. Mereka mengoptimalkan pemanfaatan sumber belajar digital dalam pembelajaran sejarah di masa pandemi Covid-19, memberikan keleluasaan dan kemandirian dalam belajar. Peserta didik diajak untuk mengeksplorasi, berkreasi, dan mempelajari lebih dalam tentang sejarah digital dengan mempelajari sumber daya melalui sejarah Digital.